AI-Driven Empowerment in Muslim Communities: A Prisma Statistical Review of Love-Based Educational Transformations in Indonesian Madrasahs - Adiyono, Adiyono; Hendawi, Manal; Sholeh, Makherus; Prasetyo, Nova Tri (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2025)
Artificial intelligence rapidly penetrates Indonesian madrasahs, a significant concern is how to balance technological advancement with the ethical and spiritual values of Islamic education. However, one significant gap is the integration of AI within the Love-based Curriculum (LBC). The current status will fill this gap through a systematic literature review (SLR) for future studies, guided by the PRISMA framework and incorporating statistical synthesis with an operational design. We systematically analyzed 47 articles included in the general analysis from 2013 to 2025, indexed in Scopus, Web of Science, Dimensions, DOAJ, and Google Scholar databases, using quantitative coding and bibliometric mapping. Results indicate a moderate correlation, positive yet not stringent (quantitative metrics from included studies), between AI adoption and LBC-driven curriculum innovation, with predominant themes of empathy, spiritual regulation, and collaborative compassion. The results reveal a 340% increment in publications related to the theme after 2018, although only seven records (9.7% of the total) document the AI-LBC. This review yields an original evidence synthesis, indicating that artificial intelligence, when ethically aligned with LBC principles, would significantly enhance value-centered learning and empowerment of communities in madrasahs.